Comparison of the efficacies of polycaprolactone filler and lidocaine‐added filler on neocollagenesis in a rat model. (11th December 2021) - Sezer, Suat; Sarac, Gulbahar; Gul, Mehmet; Zayman, Emrah; Kapicioglu, Yelda
Abstract: Background: Polycaprolactone (PCL) is a semi–permanent filler stimulating neocollagenesis. Lidocaine is frequently used to reduce the pain and, however, may have negative effects on collagen. It was aimed to compare the histological changes on rat skin and efficacies of PCL filler and lidocaine addition. Objective: In this study, results of PCL and PCL+Lidocaine application on rat skin were compared using hematoxylin–eosin (H&E) staining, Masson's trichrome (MT) staining, and electron microscope (EM). Methods: A total of 30 adult female rats were divided into three groups: the control group, the PCL group, and the PCL+Lidocaine group. The tissue samples taken at months 2 and 4 were examined using H&E, MT, and EM. Results: At month 2, dermis thickness, fibroblast count, and collagen fiber diameter increased similarly in the PCL and PCL+Lidocaine groups. Collagen fiber diameter was significantly higher in the PCL group than in the PCL+Lidocaine ( p :0.016) and control groups ( p :0.009). At month 4, no significant difference was detected between the PCL and PCL+Lidocaine groups in terms of fibroblast count, collagen fiber count, and collagen fiber diameter; dermis thickness was lower in the PCL+Lidocaine group at month 4 ( p < 0.46). Dermis thickness, fibroblast count, collagen fiber count, and collagen fiber diameter were found to be significantly lower than in the PCL and PCL+Lidocaine groups. Conclusions: Our study showed that lidocaine addition to PCL filler does not affect the efficacy of the filler and PCL filler stimulates neocollagenesis.